2020
DOI: 10.1186/s12879-020-4913-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation of prevalence of malaria, parasite density and the multiplicity of Plasmodium falciparum infection throughout the year at three different health centers in Brazzaville, Republic of Congo

Abstract: Background In the Republic of Congo, hot temperature and seasons distortions observed may impact the development of malaria parasites. We investigate the variation of malaria cases, parasite density and the multiplicity of Plasmodium falciparum infection throughout the year in Brazzaville. Methods From May 2015 to May 2016, suspected patients with uncomplicated malaria were enrolled at the Hôpital de Mfilou, CSI « Maman Mboualé», and the Laboratoire National de Santé Publique. For each patient, thick blood wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
4
8
1
Order By: Relevance
“…The studies in Ghana were actually carried out on asymptomatic populations with increased MOI values compared to symptomatic populations on whom the present work is based. Unlike this study, no seasonal fluctuation of the MOI was reported in the Democratic Republic of the Congo [ 38 ] highlighting the geographical differences in the expression of the MOI. That is probably why the MOI is not a reliable indicator of malaria transmission in areas with reduced intensity of malaria transmission [ 37 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The studies in Ghana were actually carried out on asymptomatic populations with increased MOI values compared to symptomatic populations on whom the present work is based. Unlike this study, no seasonal fluctuation of the MOI was reported in the Democratic Republic of the Congo [ 38 ] highlighting the geographical differences in the expression of the MOI. That is probably why the MOI is not a reliable indicator of malaria transmission in areas with reduced intensity of malaria transmission [ 37 ].…”
Section: Discussioncontrasting
confidence: 83%
“…The predominant alleles were K1-type alleles for msp-1 and FC27-type alleles for msp-2 . These findings are consistent with previous reports for Madagascar [ 14 ] and other settings in Africa (Nigeria [ 18 , 26 ], Congo Brazzaville [ 29 ], Mauritania [ 30 ], Benin [ 31 ], Gabon [ 32 , 33 ], Ivory Coast [ 34 ], Cameroon, [ 35 ], Ethiopia [ 36 39 ]), India [ 40 ], and Southeast Asia [ 41 ]. However, they contrast with recent reports from Myanmar [ 42 ], where MAD20 and 3D7 were the most prevalent alleles.…”
Section: Discussionsupporting
confidence: 92%
“…The high prevalence of false negative RDT results recorded by both the UsmRDT and the mRDT could have been due to the presence of low parasite densities, below their respective lower limit of detection. Low-density parasites are prevalent in asymptomatic parasite carriers during the off-peak malaria season [ 46 ]. The presence of parasites with pfhrp 2 gene deletions could also result in false negative RDT results [ 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%